What is digital history? - Salmi, Hannu (Medford Polity Press, 2021)
The first student handbook on digital methods and sources for historians"--
Includes bibliographical references (pages 93-119) and index.
Keywords: History -- Computer network resources; History -- Methodology; History -- Research